School Management Strategies in Dealing with Juvenile Delinquency Issues: Preventive and Curative Approaches - Masut, Vinsensius Rixnaldi; Sunarni, Sunarni (Universitas Negeri Malang, 2025)
This article aims to identify school management strategies in addressing juvenile delinquency through preventive and curative approaches, considering the important role of schools as the second environment after family in shaping student behavior. Juvenile delinquency has become a complex issue in the school environment, often influenced by various internal and external factors, such as family background, peer environment, and the quality of guidance provided. This study employs a qualitative method with a literature review approach to examine various research and theoretical concepts related to school management strategies in dealing with juvenile delinquency. Data collection in this study was conducted using documentation techniques combined with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach to ensure a systematic process of literature search and selection. Research findings indicate that preventive approaches, such as character education, strict rule enforcement, and proactive counseling, are effective in preventing students from engaging in deviant behavior. On the other hand, curative approaches are also important in addressing students already involved in delinquency through intervention actions, counseling, and collaboration with external parties such as psychologists or counselors. Both approaches complement each other in creating a school environment that supports positive change in students.